Follicular lymphoma regulatory T-cell origin and function - Stéphane Rodriguez; Mehdi Alizadeh; Claire Lamaison; Alexis Saintamand; Céline Monvoisin; Rachel Jean; Rachel Jean; Laurent Deleurme; Laurent Deleurme; Jose Ignacio Martin-Subero; Céline Pangault; Céline Pangault; et al. (Frontiers in Immunology, 2024)
IntroductionFollicular Lymphoma (FL) results from the malignant transformation of germinal center (GC) B cells. FL B cells display recurrent and diverse genetic alterations, some of them favoring their direct interaction with their cell microenvironment, including follicular helper T cells (Tfh). Although FL-Tfh key role is well-documented, the impact of their regulatory counterpart, the follicular regulatory T cell (Tfr) compartment, is still sparse.MethodsThe aim of this study was to characterize FL-Tfr phenotype by cytometry, gene expression profile, FL-Tfr origin by transcriptomic analysis, and functionality by in vitro assays.ResultsCD4+CXCR5+CD25hiICOS+ FL-Tfr displayed a regulatory program that is close to classical regulatory T cell (Treg) program, at the transcriptomic and methylome levels. Accordingly, Tfr imprinting stigmata were found on FL-Tfh and FL-B cells, compared to their physiological counterparts. In addition, FL-Tfr co-culture with autologous FL-Tfh or cytotoxic FL-CD8+ T cells inhibited their proliferation in vitro. Finally, although FL-Tfr shared many characteristics with Treg, TCR sequencing analyses demonstrated that part of them derived from precursors shared with FL-Tfh. DiscussionAltogether, these findings uncover the role and origin of a Tfr subset in FL niche and may be useful for lymphomagenesis knowledge and therapeutic management.